HUMAN ANATOMY AND PHYSIOLOGY: STRUCTURE-FUNCTION HARMONY - Mahsudov Valijon Gafurjonovich (TADQIQOTLAR, 2026)
Abstract: This work is devoted to the study of the harmony of structure and function between human anatomy and physiology, showing that the structure of cells, tissues, organs and organ systems determines their physiological functions. The study highlights the principle of structure-function as one of the basic concepts of biomedical sciences and analyzes the adaptation of anatomical features in the human body to specific functional needs. The connection between structure and function is explained using the example of the cardiovascular, respiratory, nervous and musculoskeletal systems. Understanding this connection is important for the formation of clinical thinking for medical students. It is also emphasized that disorders in anatomical structures lead to disruption of physiological functions and form the basis of many diseases. In general, the integration of anatomy and physiology serves to provide a deeper understanding of the human body and increase the effectiveness of medical education.